Pengembangan Sistem Informasi Manajemen Konstruksi pada PT. AA Bersaudara - Reza Yoanda; Djoko Pramono; Bondan Sapta Prakoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
PT. AA Bersaudara is a construction company based in Palembamg, South Sumatera that provides construction services to build various facilities that needed by government or private institutions and organizations. In running its business, the company is required to manage its resources in order to achive its goal to keep the project on schedule. To address this need, the company requires a system that can accurately track and record project activities in real-time. This can help project stakeholders make the right decisions quickly. Based on this problem, a construction management information system was developed that can be used by project stakeholders, such as project managers and field managers, to manage project planning and activity data. In addition, project owners and company management can see the progress report of a project being carried out. The throw-away prototyping method was utilized in the development for this research because the users are not familiar with the use of information systems. Thus, the initial prototype developed can quickly give users an idea of how the system will be developed further. Therefore, the design made is suitable for the needs of the users based on input on the prototype made. Subsequently, the design that has been made is implemented into a complete information system and tested using testing techniques to validate that the system meets the needs of the users.